Development and validation of a multi-dimensional scale to measure the factors influencing fintech firms’ capacity to impact digital financial inclusion - Ravi, Roshan; Pandey, Nirakar Nath (The Economics and Finance Letters, 2024)
The purpose of the present study is to develop a multi-item scale to measure the factors that affect fintech firms’ capacity to impact digital financial inclusion. Fintech, or financial service delivery supported by advanced technology, has tremendously changed the financial services landscape. It has a potential to improve digital financial inclusion and help the poor. Digital financial inclusion is important since it ensures cost-saving digital mechanisms to provide financial services to the financially excluded and underserved populations. Following an inductive method, a qualitative study was undertaken among managerial staff in fintech firms. The scale development process involved the collection of primary data for pre-testing the questionnaire. The study identified four factors that affect a fintech firm’s capability of impacting digital financial inclusion: resources and capabilities, business models, networks and partnerships, and market and environment. Digital financial inclusion scale is composed of digital skills, access, and quality of access. The final scale consisted of sixty-four items. Though financial inclusion is usually measured from a demand-side perspective, this study provides a supply-side measure for digital financial inclusion. Thus, it can help in identifying and understanding the factors that may hamper fintech firms’ capability to attain desirable outcomes with respect to digital financial inclusion.